Kearifan Lokal "Makanan Tradisional": Rekonstruksi Naskah Jawa dan Fungsinya dalam Masyarakat - Trisna Kumala Satya Dewi (Manuskripta, 2011)
Traditional food is a cultural phenomenon. Culture plays a role in determining whether a food item is edible or not, while simultaneously labeling or legitimizing it. Thus, food is not merely for sustaining life, but also for preserving the culture of a collective group. In this context, food carries symbolic meanings associated with social and religious functions. In Javanese society, traditional food is closely linked to Javanese ritual ceremonies that continue to be practiced to this day. This is also evident in several Javanese manuscripts containing descriptions of traditional food, namely Serat Centhini, Serat Goenandrija, Serat Wilujengan, Jumenengan, Kraman, Mangkunegaran, and Primbon Lukmanakim Adammakna. These manuscripts contain various types of traditional foods and their functions within Javanese society. Through this paper, local wisdom in the form of cultural heritage—namely the thoughts of ancestors regarding traditional food as recorded in these manuscripts—will be presented. === Makanan tradisional merupakan fenomena kebudayaan. Kebudayaan pun ikut menentukan makanan dapat dimakan atau tidak sekaligus memberi cap atau mengesahkannya. Dengan demikian, makanan bukan sekadar untuk mempertahankan hidup, melainkan juga untuk mempertahankan kebudayaan sebuah kolektif. Dalam hal ini, makanan mempunyai arti simbolik yang berkaitan dengan fungsi sosial dan keagamaan (religi). Dalam masyarakat Jawa, makanan tradisional erat hubungannya dengan upacara ritual masyarakat Jawa yang hingga kini masih dilaksanakan. Hal tersebut pun nampak dalam beberapa naskah Jawa yang berisi tentang makanan tradisional, yaitu Serat Centhini, Serat Goenandrija, Serat Wilujengan, Jumenengan, Kraman, Mangkunegaran, dan Primbon Lukmanakim Adammakna. Naskah-naskah tersebut berisi berbagai macam makanan tradisional serta fungsinya dalam masyarakat Jawa. Melalui tulisan ini, akan dipaparkan kearifan lokal berupa warisan budaya, yaitu pemikiran-pemikiran nenek moyang mengenai makanan tradisional yang terekam dalam naskah-naskah tersebut.